Verbascum thapsus: Antifungal and phytotoxic properties - Vogt, Maria Veronica (2010)
Verbascum thapsus (Schrophulariaceae) better known as Mullein is a medicinal plant used in the treatment of inflammatory diseases, asthma, spasmodic cough, diarrhea, and other pulmonary problems. The objective of this study was to evaluate the effect of V. thapsus extracts on fungal plant pathogens growth and seed germination. Verbascum thapsus leaves were treated with n-hexane, chloroform, methanol, cold and warm water to obtained the extracts. Antifungal activity was observed mainly in the methanol extract (1000 µg mL-1) against Fusarium graminearum and Macrophomina phaseolina. Furthermore, results show that the hexane, cold and warm aqueous extract favored or had no toxic effect on Lycopersicon esculentum and Triticum aestivum seeds germination and growth, while the chloroform and methanol extracts affected negatively the germination.